De novo and recurrent post-transplant membranous nephropathy cases show similar rates of concurrent antibody-mediated rejection - Khorsandi, Nikka; Han, Hwarang Stephen; Rajalingam, Raja; Shoji, Jun; Urisman, Anatoly (Frontiers in Nephrology, 2024)
BackgroundMembranous nephropathy (MN) can develop post-kidney transplant and is classified as a recurrent disease in patients with a history of MN in the native kidneys or as de novo disease in patients without such history. The mechanism of recurrent MN is thought to be like that of primary MN, but the mechanism of de novo MN is not well delineated. An association between de novo MN and antibody-mediated rejection (AMR) has been suggested.MethodsA search of the pathology database from our medical center identified 11 cases of recurrent and 15 cases of de novo MN, in which clinical and histologic findings were compared. No significant differences were identified in the demographic characteristics, serum creatinine and proteinuria trends, or rates of allograft failure between the recurrent and de novo MN groups.ResultsRates of concurrent AMR were high in both groups (36% and 40%, respectively) but not statistically different from each other. PLA2R immunofluorescence (IF) positivity was seen in 64% of recurrent MN cases compared to 33% of de novo MN cases, suggesting a higher incidence of PLA2R-positive de novo MN than previously reported. No significant histologic differences were identified in the initial biopsies from the two groups, except mean IgG intensity by IF was higher in the recurrent group, suggesting a higher load of immune complex deposits at diagnosis in this group.ConclusionThe findings do not provide support for a specific association between AMR and de novo MN, but whether there is a possible link between both forms of post-transplant MN and AMR remains an unanswered question.